Optimizing Tri-Core Permanent-Magnet-Linear-Generator Direct-Drive Wave-Energy-Conversion System Design for Sea Wave Characteristics in South Coast Yogyakarta - Fransisco Danang Wijaya; Sarjiya Sarjiya; Muhammad Rifa'i Putra Sugita (International Journal of Electrical and Computer Engineering (IJECE), 2017)
According to statistical data, the south coast Yogyakarta has significant ocean wave height which can be used to generate electricity by using wave-energy-converter system. One of the simplest way to convert wave energy to electricity is using direct-drive wave-energy-conversion (WEC) system with permanent-magnet-linear-generator (PMLG). This method is simple because it doesn’t need to convert linear motion to rotational motion. However, PMLG has large electric power losses, has great weight in both of the stator and rotor, and expensive to make. In this paper, a tri-core PMLG was designed. The electric power losses in the winding, translator weight, and manufacturing cost were ideally minimized using multiobjective optimization combined with simulated annealing (SA) algorithm. Then, the design was verified using finite element analysis. The optimized design of this PMLG was simulated using sinusoidal ocean waves which usually occur in the south coast of Yogyakarta to analyze the performance of this linear generator. Simulation result has been shown that this generator can generate 911 watt peak output power at the rated condition and at the optimum load with 81.14% efficiency. This confirms that the optimized design of PMLG is suitable for direct-drive WEC with low power losses and manufacturing cost.